The Debate upon Acquiring Bilingualism Brings Excessive Advantages or Burdensome to Young Learners - Tyas Putri Anjarini; Deli Nirmala; Catur Kepirianto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
Nowadays, controversy of bilingual education system program still exist. Bilingualism remains as an issue particularly whether or not it is appropriate to be taught for young learners. Learning two languages in the same time is seen to create damaging effect into confusion for children in their age. In spite of the criticism, there are advantages which is offered from bilingual education. Seeing on how bilinguals have good deals as across many aspects such as cognitive control and linguistic knowledge whose the learners are better in problem solving and high order thinking skills, the purpose of the study is going to focus on how bilingualism is suitable or not to learn for young learners. Since young learners are in the golden age to acquire new language, linguistic knowledge and cognitive skills are effective enough to be taught. Therefore, the study focuses more on the discussion of previous research on whether or not bilingualism give difficulties or advantages to children. It will discuss by introducing English to young learners who will meet benefits or problems of bilingualism in early childhood. Keywords: Bilingual education; bilingualism; young learners; second language; early childhood.